Decoupling Land Use Intensity and Ecological Risk: Insights from Heilongjiang Province of the Chinese Mollisol Region - Binglong Wu; Fenli Zheng; Yuchen Fu; Shouzhang Peng; Xihua Yang; Lun Wang; Dennis C. Flanagan; Jiaqiong Zhang; Zhi Li (Remote Sensing)
Global land use changes and human activities have escalated regional ecological risk, yet studies on the decoupling relationship between land use intensity (LUI) and ecological risk (ERI) remain limited. This study explored the decoupling relationship between LUI and ERI from 1990 to 2020 in Heilongjiang Province and analyzed the primary driving factors of the ERI using a decoupling model and an optimal parameter geographic detector (OPGD). The results indicate significant land use changes, particularly the conversion of woodland and grassland into farmland, resulting in a net increase of 18,055.96 km2 in farmland area. The LUI in Heilongjiang Province increased by 6.43 between 1990 and 2020. The ERI exhibited a significant upward trend from 1990 to 2020, with the average index rising from 0.097 in 1990 to 0.132 in 2020. The proportion of moderate- and higher-ecological-risk areas increased by 10.6%. A decoupling analysis indicated that most regions experienced expansionary negative decoupling between the LUI and ERI, in which the ERI escalated at a faster rate than the LUI. Furthermore, the DEM and NDVI demonstrated the highest explanatory power for the ERI, both exceeding 30%, and the synergistic interaction between the DEM and NDVI amplified spatial heterogeneity by altering microclimatic conditions. This study provides crucial insights for land management and ecological conservation policies in Heilongjiang.